PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA PUSKESMAS CIKALONG - Wiandita, Miranty Mahasti; Recky, Recky (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2024)
This research aims to analyze the influence of work motivation, work area, and rewards on employee performance using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) procedure. Information is collected from respondents and explained using SmartPLS. The research results show that work motivation and work area have a positive and significant influence on employee performance, with path coefficient values ​​of 0.482 (p=0.001) and 0.422 (p=0.003), respectively. This indicates that increasing work motivation and a conducive work area can significantly improve employee performance. On the other hand, compensation does not have a significant effect on employee performance (p=0.376). This shows that the compensation provided is not enough to directly improve performance. Therefore, organizations are advised to focus more on increasing motivation and work areas to increase productivity. Keywords: Work Motivation, Work Environment, Compensation, Employee Performance, SEM-PLS